Intersections History, Memory, Discipline - Lal, Brij V. (ANU Press, 2012)
"A wonderfully rich, insightful and personally touching collection of essays by the Pacific region's most prolific and engaging historian. Brij Lal writes eloquently and poetically about his professional and political journeys, and the many different people and worlds he has encountered on the way. Readers will be inspired by this collective account of a courageous life committed to the achievement of democratic freedom and social justice. What shines through these pages is Lal's love of and commitment to Fiji, from which he has been painfully exiled." - David Hanlon, Professor of History & Former Director of the Center for Pacific Islands Studies, University of Hawaii at Manoa. "Intersections is a compilation of Brij Lal's essays where academic knowledge combines with life world experience. The voice behind these essays is always courageous and the writing itself indicative of a highly disciplined mind. Read this book with an open mind as Lal explores with sensitivity a country he loves intensely and as he reminisces on the vocation of a scholar. Savour the book's historical insights, enter into its subaltern worlds, debate and challenge its findings, and in that moment of engagement shed a tear for a country which has lost its memory." - Vijay Mishra, Professor of English, Murdoch University "Brij Lal is a master craftsman and all his skills are on display in this fascinating work which blends autobiography with social, political and historical analysis to produce a work of impeccable scholarship. Lal emerges as much more than a historian as he reflects on the discipline of History, the changing nature of academic life, the challenges of the Indian diaspora, indenture and his travels. He may be banned from his homeland, but somehow one gets the impression that his influence is alive in Fiji, his adopted Australia and across the world. True to his indentured roots, he is still digging, still writing, and still making history." - Goolam Vahed, Associate Professor of History, University of KwaZulu-Natal